PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BUANA CIPTA PROPERTINDO - Elfrika Br Sembiring (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The purpose of this study was to determine the effect of motivation and job satisfaction on employee performance at PT Buana Cipta Propertindo by using the Saturated Sample technique with a significant 5% of 149 respondents who were employees at PT Buana Cipta Propertindo. The data collection method is by questionnaire. Data quality in this study uses the validity and reliability test, the classic assumption test and the influence test in this study using multiple linear regression analysis and coefficient of determination analysis (R2), while the hypothesis testing in this study uses (t test) and (F test) by using the SPSS software program version 22. The results of the coefficient of determination (R2) obtained from motivation and job satisfaction variables have an effect of 71.5% on employee performance. The results of the multiple linear regression test show that motivation (X1) has an effect of 76.7% of employee performance (Y) and product quality (X2) have an effect of 9, 7% of employee performance (Y). From the results of the t test and F test, it can be concluded that motivation has a partially significant effect on employee performance and job satisfaction has a partially significant effect on employee performance, and motivation and job satisfaction together have a significant simultaneous effect on employee performance at PT Buana Cipta Propertindo.